อิทธิพลของรังสีแกมมาต่อการพัฒนาพันธุ์คาลล่าลิลลี่ - อ่อนศรี กษิดิ์เดช; จันจุฬา ณัฐพงค์ (Thai Journal of Science and Technology, 2020)
Calla lily is a tuberous perennial plant that grows under high humidity. Thailand has many different colors of Calla lily. Its new varieties can be induced by breeding, using radiation or chemical mutations. The aim of this study is to induce Calla lily in sterility under the condition of acute gamma ray. The pieces of Calla lily were grown on MS feed for 14 days. The gamma irradiation doses were 0, 20, 40 and 60 gray. The results showed that the survival rates decreased with the increase of gamma ray doses of 20, 40 and 60 gray. In addition, both gamma ray doses of 20 and 40 gray could conduct 15 % mutation. It is suggested that Calla lily new varieties can be induced by acute gamma ray, resulting in a breeding for value added Calla lily.